2017
DOI: 10.1016/j.engfracmech.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth mechanisms at the microstructure scale in as-fabricated and heat treated Ti-6Al-4V ELI manufactured by electron beam melting (EBM)

Abstract: Electron beam melting (EBM) is a metal powder bed fusion additive manufacturing (AM) technology that fabricates parts by selectively scanning consecutive powder layers with an electron beam. Additive manufacturing technologies are increasing in importance for aerospace and medical applications, where the demand for a fundamental understanding and predictability of static and dynamic material properties are high. Ti-6Al-4V is the most widely used and studied alloy for this technology, and is the focus of this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 34 publications
3
30
0
7
Order By: Relevance
“…Moreover, this may explain the low FCGR values observed in Cain 3 [40] and Van Hooreweder [52]. However, Cain 1 [40] has the same orientation to Leuders 2 [32] but the FCGR in Cain 1 is comparable to Cain 2, which has a grain and layer orientation, which according to Galarraga et al [55] should produce higher FCGR values. This may be attributed to the influence of residual stresses.…”
Section: Micro-mechanism Contributionmentioning
confidence: 70%
See 2 more Smart Citations
“…Moreover, this may explain the low FCGR values observed in Cain 3 [40] and Van Hooreweder [52]. However, Cain 1 [40] has the same orientation to Leuders 2 [32] but the FCGR in Cain 1 is comparable to Cain 2, which has a grain and layer orientation, which according to Galarraga et al [55] should produce higher FCGR values. This may be attributed to the influence of residual stresses.…”
Section: Micro-mechanism Contributionmentioning
confidence: 70%
“…Nevertheless, more favourable microstructures to crack growth have been shown to be bimodal and lamellar microstructures. In order to obtain a deeper understanding on the influence of grain boundaries and layer orientation, in conjunction with a lamellar microstructure on crack growth, the work of Galarraga et al [55] on EBM-manufactured material has been reviewed. Based on the results arising from this study and the understanding around the effect of SLM-manufactured material build orientation, it can be concluded that it is important crack growth occurs perpendicular to the build layers and, if possible, orientated in the same direction as the elongated grains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the machined and HIP-processed samples, once the cracks nucleated, the cracks could propagate along α/β interfaces or across α colonies. The α phase plates also could defl ect the direction of crack growth depending on the orientation between crack tip and α colonies [26] . Hence, the crack propagation path in Fig.…”
Section: (A) (B)mentioning
confidence: 99%
“…It is necessary to provide wide complex of researches and tests. Titanium alloys are used in the following additive technology: melting layer by layer powder by electron beam (EBM) [1,2] or laser (SLM, SLS methods) [3,4], feeding melted powder or wire by plasma arc [5,6] or laser (DMLD) [7,8]. We suggest using laser metal deposition technology for manufacturing of titanium parts.…”
Section: Introductionmentioning
confidence: 99%